Optimalisasi Peran Guru dalam Motivasi Belajar Membaca untuk Siswa Kelas I SDN Logung - Khilyatussaadah Khilyatussaadah (Diksi: Jurnal Pendidikan dan Literasi, 2026)
Reading motivation is an essential factor influencing the success of elementary school students in developing literacy skills. However, there are still lower-grade students who demonstrate low motivation and limited reading ability, requiring special attention from teachers. This study aimed to describe the roles of teachers, the efforts they undertake, and the challenges they face in improving students’ motivation to learn reading in Indonesian language lessons among first-grade students at SDN Logung during the 2022/2023 academic year. This research employed a qualitative approach using a field research design. Data were collected through interviews, observations, and documentation involving the principal, first-grade teacher, and students as research participants. The findings revealed that teachers play multiple roles as instructors, educators, mentors, classroom managers, motivators, and facilitators in enhancing students’ reading motivation. The strategies implemented included coordinating with parents, incorporating ice-breaking activities and word-guessing games, placing students with limited reading skills near the teacher, providing a classroom reading corner, and utilising visual learning media such as educational posters and pictures. The study also identified several challenges, including low interest and enthusiasm among some students toward reading activities and insufficient parental involvement in supporting children’s learning at home. These findings imply the importance of strong collaboration among teachers, parents, and a supportive learning environment to sustainably improve students’ reading motivation and literacy skills at the elementary school level